Application of EPS geofoam in rockfall galleries: Insights from large-scale experiments and FDEM simulations. Issue 4 (August 2022) - Yan, Shuaixing; Wang, Yu; Wang, Dongpo; He, Siming
Abstract: Expanded polystyrene (EPS) geofoam presents a promising application in the protection of galleries against rockfall. This paper focuses on experimental and numerical studies that aim to more effectively characterise the impact kinematics between single-block rockfalls and galleries with homogeneous sand and EPS, as well as the EPS–sand composite cushion system. The compression, tensile, and shear properties of EPS are firstly recognised with mathematical descriptions. Then, large-scale experiments considering the rock block mass and velocity help illustrate the general features of impact processes, and quantify the structural dynamic responses as well as the energy dissipation of the cushioning. Finally, the combined finite and discrete element method (FDEM) is first adopted to simulate the combined failure modes of EPS subjected to impact. The numerical model is well verified and exhibits great predictability in the contribution of different materials in the composite cushion system to energy dissipation. The results demonstrate the effective impact resistance of the EPS-sand cushioning. Additionally, they engender an extended methodology for analysing more EPS-based composite cushion systems applied in rockfall galleries. Highlights: The impact kinematics between rockfalls and galleries with different cushions are fully interpreted by large-scale tests. FDEM is first used to simulate the impact failure modes of EPS and quantify the energy dissipation in composite system. The penetration depth significantly affects the energy dissipation performance of EPS-sand composite cushion.